Covid-19: Implications for professional women's football (2020)
FIFPRO`s top priority regarding Covid-19 is public health and safety. We also recognize our unique position as the global players union for professional footballers to demonstrate the highest standard of leadership in sport as the world addresses this pandemicand its impacts. Several weeks into the crisis it is evident that the spread of the virus has impacted all levels of the football economy as well as the health and well-being of players. FIFPRO`s 2020 Raising Our Game report, on improving industry standards for professional female players, was originally scheduled for publication in February 2020 and is now postponed to April due to the global health crisis. The findings draw on information collected from multiple sources and through various methods, including a player survey, stakeholder surveys, primary interviews with executives and experts, and secondary research focusing on women`s football. The report captures the recent growth and development of the women`s football industry, demonstrating the significant upward trends that the women`s game had recently begun witnessing prior to the pandemic. Its emphasis on setting global labour standards and protecting players` rights and wellbeing, with the common objective to safeguard the women`s game, is more relevant now than ever.We have written this supplement to address our findings from the report in light of the present situation. This briefing provides perspective on the evolving situation, implications of the global health crisis on professional women`s football, and recommendations for an open, collaborative approach that seeks and appreciates the view of the players in establishing solutions.